La scrittura filosofica di Guido D. Neri (Materiali di Estetica. Terza serie, 2016)
Working on the principle that the style of writing outlines any trace of truth, I read Guido Neri’s works in order to reconstruct the expressive style of his writing as a sign of his peculiar way to engage himself philosophically. I have dwelled on certain issues: first of all the step backward recognized in his attention to get back to the symbolic conditions of the expressiveness of the reality; then the obliquity of the style as figure of an embodied relationship with the world. Thirdly his philosophical appointment, in dialogue with others and with the verticality of historical time, accompanied by a clear and exalted work of writing through which he has constantly taken distances from the feature of a philosophical writing expert. Finally I showed some hot topics of his thought that crossed it as the main themes both of his working and of his life: I refer in particular to the passivity and to the aesthetic experience.